A mild and practical method for deprotection of aryl methyl/benzyl/allyl ethers with HPPh2 and tBuOK. Issue 35 (25th August 2021) - Pan, Wenjing; Li, Chenchen; Zhu, Haoyin; Li, Fangfang; Li, Tao; Zhao, Wanxiang
Abstract : Aryl methyl/benzyl/allyl ethers with various functional groups reacted smoothly to afford deprotected products in high yields, and further investigation showed that deallylation is easier than debenzylation and demethylation. Abstract : A general method for the demethylation, debenzylation, and deallylation of aryl ethers using HPPh2 and t BuOK is reported. The reaction features mild and metal-free reaction conditions, broad substrate scope, good functional group compatibility, and high chemical selectivity towards aryl ethers over aliphatic structures. Notably, this approach is competent to selectively deprotect the allyl or benzyl group, making it a general and practical method in organic synthesis.